Influence of crystal anisotropy and process parameters on surface shape deviation of sapphire slicing - Chao WANG; Peiqi GE; Jikai He; Xinhui WANG (Jin'gangshi yu moliao moju gongcheng, 2023)
Due to the anisotropy of sapphire crystal material, the mechanical properties vary in multi-wire saw slicing based on different cutting positions. This variation leads to the deviation of the diamond wire in the vertical feed direction, resulting in the surface shape deviation of the sapphire wafers. To further investigate the influence of crystal anisotropy on the surface shape deviation of the wafer, the properties of sapphire crystal material were analyzed, and the distribution of the elastic modulus of its common crystal surfaces was calculated. By simulating the sawing force, the surface shape deviation of the wafer was calculated, and the influence of process parameters on the surface shape deviation was analyzed. The results show that the surface shape deviations of wafers cut from the C-plane, A-plane, and M-plane are not affected by the anisotropy of sapphire. A feed angle of 90° or 270° can be selected to obtain a small surface shape deviation during the slicing process of the R-plane. Additionally, reducing the specific feed rate or adopting the variable speed feed method can reduce the wafer's surface shape deviation.